The use of the Erbium Yag Laser in the Treatment of Acne Scar for Female Patients - et. al., Hanaa Hasan Kadhim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Er: YAG laser wavelength (2940nm) was used of treatment acne scar to different type. there are many different characteristic, which related to the skin layer, such as the stimulated of the skin. The presented article discusses the technical aspects of the utilization of the Er: YAG laser, its preferential utilization has been most common in the dermatology areas, as well as the possible and side effects and hazards. Below are the photographs of the patients under this study before and after Er: YAG acne scar skin resurfacing. All of the patients had mixed trophic acne scar types, which include the boxcar, ice pick, and rolling scars, even though, some certain type is predominating, which is why, it is utilized for the classification of patients in accordance. The difference in the protocols of treatment in addition to the scales of the evaluation that are utilized for the determination of the acne scarring severity in numerous clinical trials have made it difficult comparing the effectiveness of the variety of the fractional lasers that exist for treating the acne scars. In addition to that, studies that investigate the role of Erbium: YAG laser as the main choice in treating the atrophic acne scars are quite limited. which included 12 patient aged 18-25 years with the atrophic facial acne scars with Er: YAG laser. The acne scarring is one of the common dermatological conditions, causing cosmetic and psychological problems.